Correctly select the steps to solve the given equation.

3x−7−2x+5=6


*Remember to include to optional first step.*

1 answer

To solve the equation \(3x - 7 - 2x + 5 = 6\), here are the steps:

Optional First Step: Combine like terms on the left side.

  1. Combine the \(3x\) and \(-2x\) terms: \[ (3x - 2x) + (-7 + 5) = 6 \] This simplifies to: \[ x - 2 = 6 \]

  2. Next, isolate \(x\) by adding \(2\) to both sides: \[ x = 6 + 2 \] This simplifies to: \[ x = 8 \]

So the solution to the equation is \(x = 8\).